Thermal performance evaluation of recycled salt hydrates through T-history - Charles A. Wesemann; Tessa Junggeburth; H.J.H. Brouwers (Case Studies in Thermal Engineering)
Recycled magnesium sulfate heptahydrate, sourced from chemical byproducts in the nano-silica extraction from olivine, exhibits unique minor phases and reduced purity compared to analytical-grade counterparts. This study investigates phase stabilizer usage, titania as a nucleating agent, and carboxymethyl cellulose (CMC) as a stabilizing gel, to enhance the functionality of recycled salt hydrates for thermal energy storage applications. Thermocouple measurements over ten heating and cooling cycles reveal distinct thermal characteristics, with observable latent heat manifesting as a critical indicator for melting-crystallization cycling. The addition of titania increases the number of functional cycles of recycled samples but diminishes performance in analytical samples. Suggesting it provides another function other than nucleation. Statistical analysis shows an exponential decay in thermal cycles (R2 > 0.84) with increased cycles. While titania shows promise, gel stabilizers like CMC did not yield meaningful results. The average latent heat storage of the recycled epsomite was 285.4 ± 37.1 J/g. This study addresses a previously unexplored area and highlights the potential of nucleating agents in improving the functionality of recycled salt hydrates for sustainable thermal energy storage.